Pengembangan Aplikasi Sistem Informasi Akademik (Studi Kasus Smp Negeri 1 Enam Lingkung) - Z, Faredna; Adri, Muhammad; Sriwahyuni, Titi (Jurnal Teknik Komputer dan Informatika, 2021)
The development of technology has brought changes in various areas of human life. The development of this technology which provides a diverse impact to a wide range of domains of life including in the realm of education. No exception to the information system of academic in SMP Negeri 1 Enam Lingkung. After conducting research and interviews with teachers about information system that are running at the school. It can be seen at this time in SMP Negeri 1 Enam Lingkung that teachers, staff, students and academic grades data still use manual in processing, so the process will take a long time. To overcome it, an information system of academic application are built for SMP Negeri 1 Enam Lingkung. This information system of academic using the PHP programming language with CodeIgniter Framework in designing, the software development code generator or editor of its use Sublime Text 3, MySQL as database design, as well as Xampp-win 32-1.6.8 for the connections. This final project produced an information system application that provides the facilities of information for the member of school to managing information such as the data of teachers, staff, students and students' academic grades to be a report card.